Performance of Mutual Funds in India: A Study with Reference to Select Equity Multi-Cap Funds - Sourav Kumar Das; Das, Samyabrata; Seth, Samarpita (Management Journal for Advanced Research, 2023)
Indian Mutual Fund Industry has witnessed enormous expansion in terms of growth of Assets under Management (AUM), from a meagre Rs. 25 crores in 1964 to Rs. 36.59 lakh crores in August 2021. Equity Multi-cap mutual funds tend to invest in stocks of companies across the stock market irrespective of sector and size. As a result, these funds provide much-needed diversification. In a direct plan, the investor decides to invest directly in mutual funds without routing the investment through any distributor or agent. Due to the absence of an intermediary commission, the direct plan has a lower expense ratio than a regular plan which leads to higher returns. Since the outbreak of COVID-19, the stock markets have experienced an extensive crisis with severe dampening effects in the entire global scenario. It has affected the Indian Mutual Fund Industry as well. However, irrespective of all negative signs, the impact of COVID-19 has created a ray of hope towards rebuilding self-confidence for Indian investors during the last year in this new normal landscape. In this backdrop, the present research paper focuses on examining the performance of direct plans of four open-ended Equity Multi-cap Mutual Funds [Baroda Multi-Cap Fund (BMF), ICICI Prudential Multi-Cap Fund (IPMF), Invesco India Multi-Cap Fund (IIMF) and Nippon India Multi-Cap Fund (NIMF)] based on certain parameters. This secondary data-based study covers 8 years (2013-2021). The criterion for selecting the funds was net assets above Rs.1,000 crores as of 31.08.2021. Results reveal that the funds provided double-digit returns during the entire study period. IPMF and NIMF performed poorly and remained riskier than the benchmark during the entire study period. Further, NIMF remained the riskiest fund throughout the study period. IIMF remained the best performer in the 1-year, 5-year and 8-year periods in terms of risk-adjusted return. NIMF remained the most aggressive fund and BMF remained the most defensive fund during the entire study period. The fund managers of IIMF succeeded in quality stock-picking in 1-year, 5-year and 8-year. The fund managers of NIMF performed miserably throughout the study period and failed in quality stock picking. RSQ values portray that BMF was the most successful fund in terms of diversification during the entire study period.